The interactive effects of rainfall, nutrient supply and defoliation on the herbage yields of Sahelian rangelands in north-east Mali - Hiernaux, Pierre H.Y.; Leeuw, P.N. de; Diarra, L. (International Livestock Centre for Africa, 1995)
In the Sahelian rangelands biomass production is constrained by soil moisture in the drier (100-250 mm) parts and by soil nutrients in the wetter parts. Similarly, for a given Sahelian range, nutrient deficiency would be more prominent in good than in poor rainfall years. To test this hypothesis, fertiliser trials were carried out at sites distributed along the bioclimatic gradient in the Gourma (Mali) over contrasting rainfall years between 1988 and 1992. In good rainfall years, adding 100 kg nitrogen (N) and 38 kg phosphorus (P)/ha increased herbage production by approximately 30 percent, whereas the response to fertiliser was inverted in poor years. Plant uptake of N and P increased with biomass yield, but at a lower rate. Fertiliser N and P increased biomass and nutrient yields but the nutrient content in biomass decreased due to nutrient dilution. In the pastoral context of the Sahel, grazing further influences the interactive effects of moisture and nutrient supply on herbage production and quality. To elucidate these interactions, cutting experiments were conducted with and without fertilisers. The effects of defoliation without fertilisers depended on rainfall and frequency of cutting. In fair rainfall years early cuttings increased total yield whereas early cutting reduced yield in poor rainfall years. In good rainfall years total yield was reduced by 50 and 25 percent when repeated cuttings were at 15- and 30-day intervals, respectively. Reductions in yields were less severe in poor rainfall years. N and P uptakes changed little with repeated cuttings due to higher nutrient contents in regrowth. Adding fertilisers increased regrowth yields so that cummulative yields of repeated cuttings equalled or exceeded the control yield, depending on the rainfall conditions. Redistribution of rainfall in the landscape by run-off/run-on, and livestock grazing behaviour diversify the quantity and quality of range resources. Thus, recognising that soil nutrients provide a constraining ceiling for primary and secondary productivity on a regional scale, exploiting the quality gradient on a local scale through range management provides room for production improvement with little risk for this ecosystem.